The Double Burden: Food Insecurity and Depressive Symptoms in a Rural Community of Southern India - Kumar Guru Mishra; Nabnita Patnaik; Bobba Harshitha; Anu Mohandas; Adrija Roy; Snigdha Patnaik (Journal of Pharmacy and Bioallied Sciences)
Introduction: Food insecurity has been linked to adverse mental health outcomes, particularly depression. However, there is a paucity of community-based studies investigating this association, especially in southern India. This study aimed to estimate the prevalence of food insecurity and examine its association with depressive symptoms among adults in a rural village in Telangana, India. Materials and Methods: This cross-sectional study recruited 537 participants aged 18–60 years from Moinabad village using a multistage cluster sampling technique. Food insecurity was assessed using the Food Insecurity Experience Scale, and depressive symptoms were measured using the Hamilton Depression Rating Scale. Sociodemographic data, including age, gender, educational attainment, addiction history etc., were collected, and logistic regression analyses were performed to evaluate the association between food insecurity and depressive symptoms, adjusting for potential confounders. Results: The prevalence of food insecurity was high at 86.21%. A significant finding was the strong positive association between increasing food insecurity levels and presence of depressive symptoms. Compared to the food-secure group, those with moderate food insecurity had 10.55 times higher adjusted odds ratio (aOR) (aOR = 10.55, 95% confidence interval [CI]: 1.25–82.64) and those with severe food insecurity had 9.26 times higher aOR (aOR = 9.26, 95% CI: 1.16–71.78) of having depressive symptoms. Conclusion: This study reveals a high prevalence of food insecurity, disproportionately affecting vulnerable groups. It establishes a strong positive association between increasing food insecurity levels and depressive symptoms, highlighting the detrimental impact on mental health. Other risk factors for depression include sociodemographic characteristics such as older age, female gender, lower educational level, and addiction history.